PRODUCTION OF AM FUNGI USING IN VITRO CULTURE TECHNIQUES - AJAY PAL; SONALI PANDEY (International Journal of Pharma and Bio Sciences, 2016)
The most abundant members of the soil organism that develop beneficial relationships with plants roots and contribute majorly to plant development are called mycorrhizal fungi. The most common well-known of these relations are the Vesicular Arbuscular Mycorrhizae (VAM).The obligate biotrophic nature of AM fungi has long been accepted. The helpful effects of AM Fungi on the growth and health of plants is recognizing VAM for some time, although their obligate biotrophic nature has limited. It’s in vitro culture and large-scale production, reducing their potential for utilize as inocula in agricultural and horticultural practices has provided new tools for growing AMF under in vitro conditions, such as root organ culture and the monoxenic method involved growing sterile with AMF spores. Root organ culture has obvious advantages over conventional systems, permitting production of contaminant-free propagules. Many AMF species are successfully cultivated in monoxenic culture. In vitro culture of VAM fungi under axenic conditions continues to be one of the most challenging goals of modern biology. The in vitro systems have proved to be a helpful tool to study fundamental and practical aspects of AM symbiosis.